A Cross-disciplinary review of product recall research: A stakeholder-stage framework. (July 2022) - Li, Huashan; Bapuji, Hari; Talluri, Srinivas; Singh, Prakash J.
Highlights: Current product recall research has focused on managers, shareholders, and consumers, but has paid limited attention to other equally important stakeholders such as suppliers, employees, competitors, media, and regulators. Researchers have predominantly examined the issues associated with the after-recall stage to minimize the consequences of recalls, while the before- and during-recall stages that prevent recalls and make them more effective are relatively underexamined. Taking an integrative approach to consider various stakeholders and multiple stages of a product recall can help future research generate useful insights for management research and practice. Future research should adopt a cross-disciplinary, cross-stakeholder, cross-stage, and cross-organizational view on the management of product recalls. Abstract: Research on product recalls has recently witnessed a sharp increase; however, this stream of research is dispersed within and outside the discipline of management. In the current article, we review this research stream by adopting a stakeholder-stage framework that draws on stakeholder theory and crisis management literature. Specifically, we summarize and integrate the product recall research along two dimensions: the stakeholders involved (e.g., managers, employees, shareholders, consumers, suppliers, competitors, media, and regulators) and the key issues at different stages of a recall (before-recall, during-recall, and after-recall). We find that current research has focused on managers, shareholders, and consumers, but has paid limited attention to other equally important stakeholders such as suppliers, employees, competitors, media, and regulators. Also, researchers have predominantly examined the issues associated with the after-recall stage to minimize the consequences of recalls, while the before- and during-recall stages that prevent recalls and make them more effective are relatively underexamined. To address these gaps and extend the current research, we develop a range of future research opportunities that can make nuanced theoretical contributions and generate implications for practice and policy. By emphasizing the need to adopt a stakeholder management approach and consider recalls as a process, rather than an event, this review paves the way for enriching future research on product recalls.